Extending Modern Portfolio Theory into the Domain of Corporate Diversification: Does it Apply? - Lubatkin, Michael; Chatterjee, Sayan (Academy of Management Journal, 1994)
It is widely held that diversification lowers a firm's unsystematic (business-specific) risk but does not affect its systematic (systemwide) risk. We tested each notion while controlling for other factors that influence risk. The findings show that the relationship between corporate diversification and both forms of stock return risk generates a U-shaped graph. Thus, an important way for corporations to minimize risk is to diversify into similar businesses rather than into identical or very different businesses.